PENERAPAN PENDEKATAN PROBLEM-BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN MOTIVASI BELAJAR SISWA - Nurhalimah, N.; Maulana, M.; Isrok'atun, I. (Jurnal Pena Ilmiah, 2017)
This study aims to improve the ability of solving mathematical problems and learning motivation in primary school through learning by using problem-based learning (PBL) approach. The method used is a free variable experimental method (quasi experimental) with design control group is not equivalent. Population in this research is all class V in Sumedang South. Meanwhile, the sample is the students of class V SDN Sukaraja I (control) and SDN Sukaraja II (experimental). Instruments used in the form of problems of mathematical problem solving skills, learning motivation attitude scale, teacher performance observation sheet and student activity, and student response questionnaire. Result of research with significance level Î± = 0,05 shows that conventional approach and PBL approach can increase the ability of mathematical problem solving and student's learning motivation. The improvement is influenced by the performance of the teacher which done well so that the students can follow the learning very good.